Analysis On Extra Low Frequency (Elf) Signal Due To Earthquake Activity - Muhammad Nabil Ashraf, Ruslan (2022)
Nature phenomena such as earthquake (EQ) release electromagnetic (EMT) wave during its process. A seismometer is often used as the detection tools for EQ detection. However due to its low detection radius, an alternative way which is by EMT wave detection is proposed. ELF sensors may detect lightning and earthquake activity with a range radius of thousand kilometers. Many data will be mixed in one ELF signal that needs to analyze and identify the EQ data based on the ELF data and from other sources. This purpose of this project is to identify the EQ from the ELF data analysis and verify with EQ activity from USGS. JAXA data was used to know the location of lightning event. Its data is used to deny lightning activity at the time of EQ occurrence. It is interested to notice that an we are able to identify an EQ activity from ELF signal for an event occurred in Sumatera Indonesia. No lightning activity are noticed from JAXA data.